Role of nitric oxide in development of fibrotic changes in rats’ testes after 270 day central deprivation of testosterone synthesis - Stetsuk, Ye.V.; Akimov, O.Ye.; Shepitko, K.V.; Boruta, N.V.; Goltsev, A.N. (World of medicine and biology. 2020; 73(3): 211-215., 2020)
Disturbance in production of nitric oxide (NO) may lead to various changes in different organs and systems. Certain clinical situations require prolonged usage of inhibitors of testosterone synthesis. Scientific literature provides limited information regarding the influence of prolonged deprivation of testosterone synthesis on production of NO and microscopic organization of rats’ testes. Prolonged central deprivation of testosterone synthesis leads to endothelial dysfunction, development of fibrosis, decreases the nitric oxide production and shifts pro-/antioxidant balance in favor of the pro-oxidants without increase in lipid peroxidation intensity. Central deprivation of testosterone synthesis leads to fibrosis with subsequent disruption of the structural organization of the convoluted seminiferous tubules, hemodynamic disturbances, endothelial dysfunction, increased density of the vascular wall of blood vessels and systemic stasis. Decreased production of NO from constitutive isoforms of NO-synthase plays major role in development of structural changes in the interstitial tissue of testes on the 270th day of the experiment. __________________________________________________________________________________________ Порушення виробництва оксиду азоту (NO) може призводити до різних змін в різних органах і системах. Певні клінічні ситуації вимагають тривалого використання інгібіторів синтезу тестостерону. У науковій літературі є обмежена інформація про вплив тривалого позбавлення синтезу тестостерону на продукцію NO і мікроскопічну організацію сім'яників щурів. Тривала центральна депривація синтезу тестостерону призводить до ендотеліальної дисфункції, розвитку фіброзу, знижує вироблення оксиду азоту та зрушує про- / антиоксидантний баланс на користь прооксидантів без збільшення інтенсивності перекисного окислення ліпідів. Центральна депривація синтезу тестостерону призводить до фіброзу з подальшим порушенням структурної організації звивистих сім'яних канальців, порушень гемодинаміки, ендотеліальної дисфункції, збільшення щільності судинної стінки кровоносних судин і системному застою. Зниження продукції NO з конститутивних ізоформ NO-синтази відіграє основну роль у розвитку структурних змін інтерстиціальної тканини сім'яників на 270-й день експерименту.
Роль оксиду азоту в розвитку фібротичних змін сімяників щурів після 270 днів центральної депривації синтезу тестостерона
Stetsuk YeV, Akimov OYe, Shepitko KV, et al. Role of nitric oxide in development of fibrotic changes in rats’ testes after 270 day central deprivation of testosterone synthesis. World of medicine and biology. 2020; 73(3): 211-215.
Keywords: testes; rats; diphereline; oxidative stress; nitric oxide; fibrosis; сімяники; інтерстиціальні ендокріноцити; сустентоцити; NO-синтаза; iNOS; cNOS; L-аргінін; супероксиддисмутаза; щури